Sensors and instrumentation, aircraft/aerospace, energy harvesting & dynamic environments testing, volume 7 : proceedings of the 38th IMAC, a conference and exposition on structural dynamics 2020 /: proceedings of the 38th IMAC, a conference and exposition on structural dynamics 2020. volume 7 ([2021]) - Unknown
No abstract available